2017
DOI: 10.1111/1756-185x.13245
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D receptor polymorphisms and systemic lupus erythematosus in an Indian cohort

Abstract: FokI and TaqI variants are significantly associated with SLE in an eastern Indian cohort. The cause-effect relationship can be assessed from the combined analyses of VDR polymorphism, plasma vitamin D levels and clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 46 publications
(101 reference statements)
1
38
0
2
Order By: Relevance
“…As vitamin D‐related response dependent on levels of vitamin and its receptor, combined analysis of 25‐OH vitamin D 3 and VDR polymorphisms are essential to decipher actual role of vitamin D molecules in heart failure. A recent study investigated combined analysis of VDR variants and levels of 25‐OH vitamin D 3 and demonstrated a significant role of VDR and plasma levels with susceptibility to SLE and lupus nephritis . In the present study also, we observed a significant combined role of VDR and plasma vitamin D with susceptibility to heart failure; subjects with VDR mutants and insufficient/deficient 25‐OH vitamin D 3 levels are likely to have heart failure compared to other combination.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As vitamin D‐related response dependent on levels of vitamin and its receptor, combined analysis of 25‐OH vitamin D 3 and VDR polymorphisms are essential to decipher actual role of vitamin D molecules in heart failure. A recent study investigated combined analysis of VDR variants and levels of 25‐OH vitamin D 3 and demonstrated a significant role of VDR and plasma levels with susceptibility to SLE and lupus nephritis . In the present study also, we observed a significant combined role of VDR and plasma vitamin D with susceptibility to heart failure; subjects with VDR mutants and insufficient/deficient 25‐OH vitamin D 3 levels are likely to have heart failure compared to other combination.…”
Section: Discussionsupporting
confidence: 77%
“…As described earlier, vitamin D receptor polymorphisms ( FokI , TaqI , BsmI , and ApaI ) were genotyped by polymerase chain reaction followed by restriction fragment length polymorphism (PCR‐RFLP). Thermocycling condition for amplification of PCR fragment was as follows: initial denaturation for 5 minutes at 95°C, followed by 35 cycles of denaturation at 95°C for 40 seconds, annealing at 60°C for 45 seconds, and extension at 72°C for 45 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common polymorphisms in vitamin D receptor (VDR) were genotyped by polymerase chain reaction followed by restriction fragment length polymorphism (PCR-RFLP), as described earlier. 48 Briefly, four sets of primers were employed for amplification of DNA fragment containing respective polymorphic site as follows gested with a respective restriction enzyme and analyzed for genotypes of subjects. Forty amplicons were randomly selected and subjected to sequencing for confirmation of genotyping methods.…”
Section: Genotyping Of Vdr Polymorphismsmentioning
confidence: 99%
“…VDR is also expressed in immunocytes, and hence, the immune-physiological effects of 1,25-(OH) 2 D 3 in various immunocytes can be implemented via binding with the VDR, which mediates the gene transcription via association with the VDRE [7]. Another piece of evidence that suggests a potential role of vitamin D in the immune system and the mediation of autoimmune diseases is that a few well-described VDR polymorphisms, namely, ApaI , FokI , BsmI , and TaqI , were demonstrated to be associated with the risk of the development of autoimmunity [24,25]. Nevertheless, data regarding the mechanism as to how VDRE affects the downstream functions of immunocytes are limited.…”
Section: Vitamin D Its Nature and Impact On Various Body Systemsmentioning
confidence: 99%